Psychosocial problems faced By thalassemia major patients of district Multan, Pakistan - Ishfaq, Kamran; Mohamad Diah, Nurazzura; Ali, Johar; Fayyaz, Bareera; Batool, Iram (Pakistan Pediatric Association, 2018)
Objective: To identify the psychosocial problems faced by thalassemia major patients in District Multan, Pakistan. Study design: A Cross sectional study Place & duration: The study was carried out at the four thalassemia Centers (i) Amina Blood Foundation (ii) Fatimid blood foundation (iii) Minhaj ul Quran (iv) Thalassemia Centre, CH&ICH Multan, Pakistan from 1st January 2017 to 30st May 2017. Methodology: Two hundred thalassemia major patients were selected through convenient sampling. Young people (age 12-18) suffering from thalassemia major and regularly attending the thalassemia centers were included. Other forms of thalassemia and refusal to participate in the study were excluded. Data was collected through structured interview and analyzed by using SPSS (Statistical Package for Social Sciences) version 21 and Chi square test was used to check the association. The questions related to psychosocial burden of thalassemia e.g. disease burden on their education, time off school, outdoor-indoor games, social activities, government support, hindrance to get blood, people’s attitude, fear of life were asked. Results: Two hundred Thalassemia major patients from four Thalassemia Centres participated in the study. Majority 123 (61.5%) were from Fatimid Foundation Multan whereas 46 (23.0%) patients belonged to Thalassemia Centre of CH&ICH Multan, 19 (9.5%) were from Amina blood foundation and 12 (6.0%) patients belonged to Minhajul Quran Multan. Significant proportion of the respondents consisted of males 114 (57%) while 86 (43%) were females. Majority 106 (53%) of the respondents family monthly income was PKR <20000 per month. Results indicated the significant association between the education level of thalassemia major patients and gender (X2=17.905a), (P=.000). Moreover there was the significant association between the male and female thalassemia patients participation in extracurricular activities (X2 =6.627a ), (P=.007). Conclusions: The study concluded that thalassemia major patients faced psychosocial burden in their life. The finding suggested that psychosocial support as well as medical help should be provided to the thalassemia major patients to minimize their burden. Social worker, doctors, nurses, volunteers must provide the psychosocial support to thalassemia major children and motivate their families.